CRITERIA FOR SELECTING VIRTUALIZATION SOFTWARE IN TEACHING UNIX-LIKE OPERATING SYSTEMS - Holovnya О.С. (Journal of Information Technologies in Education (ITE), 2015)
Unix-like operating systems tend to be one of the top platforms as far as they illustrate most of modern operating systems basic principles and usually belong to free and open source software. For the above-mentioned reasons unix-like operating systems are widely used in education, particularly in teaching operating systems in undergraduate informatics education. The purpose of this study is to formulate the criteria for selecting virtualization software for applying of this software in teaching unix-like operating systems in undergraduate informatics education. Using the formulated criteria, the contrastive analysis of virtualization technologies,including type I, type II and hybrid hypervisors based on dynamic translation, paravirtualization and both of these virtualization methods, and virtual containers. Along with virtualization technologies, alternative virtualization-free ways of teaching unix-like operating systems(installing virtualized operating system as the only system on the computer and multi-booting) are also considered. According to the obtained results the contrastive analysis of virtualization software basing on preselected virtualization technologies is done. The attention is paid on both virtualized operating systems which are placed locally and systems which are accessed over local area network or the Internet.